ASSESSMENT OF AIR POLLUTANT EMISSIONS FROM A CONSTRUCTION ENTERPRISE (CASE STUDY OF SAMARKAND UZBEKGAZSUV CONSTRUCTION LLC) (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the air pollutants emitted as a result of the activities of Samarkand Uzbekgazsuv Qurilish LLC, located in Jomboy district of Samarkand region. The enterprise emits approximately 19.01 tons of harmful substances into the atmosphere each year. The major share consists of inorganic dust (42.5%) and carbon monoxide (32.6%). In addition, sulfur oxide accounts for 12.8%, nitrogen oxide – 9.4%, and hydrocarbons – 2.6%. The asphalt production unit is the largest contributor, releasing 10.39 tons of pollutants annually.